2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:06:40
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z)计算2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z)计算2(x+y-z)-3(x-y+z)-5(x+y-z)
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z)
=6(x-y+z))-3(x-y+z)+2(x+y-z)-5(x+y-z)
=3(x-y+z)-3(x+y-z)
=3(x-y+z-x-y+z)
=3(-2y+2z)
=-6y+6z
2(x+y-z)-3(x-y+z)-5(x+y-z)+6(x-y+z) 计算
x/2=y/3=z/5 x+3y-z/x-3y+z
1.(x+y-z)+(x-y+z)-(x-y-z) 2.2x-(3x-2y+3)-(5y-2)
因式分解:25x y^2 z^2 (x+y-z)-30xyz(z-x-y)^2+5x y z^3 (z-x-y)
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..
试证明(x+y-2z)+(y+z-2x)+(z+x-2y)=3(x+y-2z)(y+z-2x)(z+x-2y)
已知(x+y)(x+z)=x,(y+z)(y+x)=2y,(z+x)(z+y)=3z,求x,y,z
(4x-2y-z)-{5x-[8y-2z-(x-2y)]-x-(3y-10z)}=?
2(x+y)(x+y-z)+3(y-z)(x+y-z)
{x+y+z=1;x+3y+7z=-1;z+5y+8z=-2
x+2y+3z=23 y-z=5 x+2z=10
设|x|-|y|+|z|=|x+y+z|,且|x+y|=4,|y+z|=5,|y|=3,求(x-y-z)^2的值
已知x/y+z=y/x+z=z/x+y,分式(x+2y+3z)/(2x+5y-2c)有意义时的值
(4x-2y-z)-{5x-[8y-2z-(x+y)]-2(3y-10z)}=?好难啊
x+y+z=35 2x-y=5 y/3=z/2 求x,y,z
(x-3y+2z)(x+3y-2z)
(x-2y+3z)(x+2y-3z)
(2y-x-3z)(-x-2y-3z)